Quantitative Water Permeability Mapping of Blood-Brain-Barrier Dysfunction in Aging - Ford, Jeremy N.; Zhang, Qihao; Sweeney, Elizabeth M.; Merkler, Alexander E.; de Leon, Mony J.; Gupta, Ajay; Nguyen, Thanh D.; Ivanidze, Jana (Frontiers in aging neuroscience, 2022)
Blood-brain-barrier (BBB) dysfunction is a hallmark of aging and aging-related disorders, including cerebral small vessel disease and Alzheimer’s disease. An emerging biomarker of BBB dysfunction is BBB water exchange rate (k W ) as measured by diffusion-weighted arterial spin labeling (DW-ASL) MRI. We developed an improved DW-ASL sequence for Quantitative Permeability Mapping and evaluated whole brain and region-specific k W in a cohort of 30 adults without dementia across the age spectrum. In this cross-sectional study, we found higher k W values in the cerebral cortex (mean = 81.51 min –1 , SD = 15.54) compared to cerebral white matter (mean = 75.19 min –1 , SD = 13.85) ( p < 0.0001). We found a similar relationship for cerebral blood flow (CBF), concordant with previously published studies. Multiple linear regression analysis with k W as an outcome showed that age was statistically significant in the cerebral cortex ( p = 0.013), cerebral white matter ( p = 0.033), hippocampi ( p = 0.043), orbitofrontal cortices ( p = 0.042), and precunei cortices ( p = 0.009), after adjusting for sex and number of vascular risk factors. With CBF as an outcome, age was statistically significant only in the cerebral cortex ( p = 0.026) and precunei cortices ( p = 0.020). We further found moderate negative correlations between white matter hyperintensity (WMH) k W and WMH volume ( r = −0.51, p = 0.02), and normal-appearing white matter (NAWM) and WMH volume ( r = −0.44, p = 0.05). This work illuminates the relationship between BBB water exchange and aging and may serve as the basis for BBB-targeted therapies for aging-related brain disorders.